The effect of lavender inhalation aromatherapy on systolic and diastolic blood pressure in patients with prehypertension - Amir Musarezaie; Mohammad Javad Tarrahi; Masoumeh Sadeghi; Sedigheh Farzi; Tahere Momeni-Ghale Ghasemi; Amir Hossein Saeidi; Maryam Sadat Shahshahani (حیات)
Background & Aim: The evidence shows that prehypertension is related to an increased risk of cardiovascular complications. This study aims to determine the effect of lavender inhalation aromatherapy on systolic and diastolic blood pressure (SBP & DBP) in people with prehypertension in Isfahan. Methods & Materials: This two-group quasi-experimental study was conducted in 2023, involving 70 prehypertensive patients selected from comprehensive health service centers in Isfahan. Participants were selected through convenience sampling and were randomly assigned to either the experimental or control group. The intervention included inhalation aromatherapy using two drops of 100% pure lavender essential oil for 20 minutes in a single session. Blood pressure measurements were taken before, immediately after, and 10 and 20 minutes post-intervention under standardized conditions. The control group received routine health center training. Data analysis was performed using SPSS software version 26, employing descriptive and inferential statistics, including repeated measures analysis of variance (RMA) and analysis of covariance (ANCOVA), with a significance level set at 0.05. Results: The results of the RMA indicated a significant interaction between time and group for both SBP (P<0.001) and DBP (P<0.001). Also, the intergroup effect for SBP was significant (P<0.001), demonstrating that the intervention group experienced a significantly greater reduction in average SBP compared to the control group. Intra-group analysis revealed a significant decrease in SBP before and after aromatherapy in the intervention group (P<0.001). In contrast, the control group did not show a significant change (P=0.068). Unlike SBP, the intergroup analysis for DBP did not yield significant results (P=0.141). Conclusion: Considering the rising trend of high blood pressure and its widespread complications, along with the positive effects of aromatherapy as a cost-effective and accessible intervention, lavender inhalation aromatherapy is recommended as a complementary treatment strategy in conjunction with other methods.